SEROLOGIC, MOLECULAR, AND PATHOLOGIC SURVEY OF PSEUDORABIES VIRUS INFECTION IN HUNTED WILD BOARS (SUS SCROFA) IN ITALY - Verin, Ranieri; Varuzza, Paolo; Mazzei, Maurizio; Poli, Alessandro (Journal of wildlife diseases, 2014)
To investigate pseudorabies-virus (PrV) –antibody and viral-DNA prevalence, we collected blood, nasal and genital swabs, and tonsillar and lymph-node tissue samples from 139 wild boars (Sus scrofa; 39 piglets, 30 juveniles, and 70 adults), during the hunting season of 2010–2011 in Tuscany, Central Italy. We performed immunohistochemistry with anti-PrV monoclonal antibodies on selected tissue samples. Forty-three of 139 (30.9%) boars were PrV-antibody positive and a 1,954–base-pair PrV-specific product was amplified from nine nasal (6.5%) and 26 genital (18.7%) swabs. Sequence analysis of PrV-positive PCR products revealed identity scores of 99–100% with Suid herpesvirus 1 strain Becker (JF797219) and confirmed the identification of PrV DNA in tested swabs. There was significantly higher antibody prevalence in adults than in juveniles and in piglets than in juveniles. The prevalence of viral DNA was significantly higher in genital swabs than in nasal specimens. The percentage of positive nasal swabs did not differ among age classes. Piglets had a higher percentage of PCR-positive genital swabs than juvenile and adult subjects (30.8% vs. 13.3% and 14.3%, respectively). Results confirmed that PrV infection is widespread in the wild boar population in the study area. The presence of anti-PrV antibodies and of the PrV virus in piglets could be related to vertical transmission of the virus. This hypothesis was also supported by a higher presence of viral genome in genital swabs than in nasal swabs. This field study supports the importance of vertical transmission of PrV, and the high prevalence of virus in genital swabs supports venereal transmission in adult feral boars.